The metatext of Bajirao Mastani : intolerance in the time of Modi. - Gehlawat, Ajay (South Asian History & Culture, 2017)
Sanjay Leela Bhansali’sBajirao Mastani(2015) utilizes an historical account to (re)tell a contemporary story. While Bhansali takes great pains to disavow any intention of religious critique, this article argues that such a critique – of fundamentalist Hindu forces – can be read as the metatext of the film. Such a metatext becomes particularly apparent in the contemporary Indian context, in which the always fraught relations between Hindus and Muslims have been further exacerbated since the 2014 election of the Hindu nationalist Bharatiya Janata Party leader Narendra Modi to the post of prime minister. In this article, I readBajirao Mastaniin light of these current events, excavating in the process the film’s metatextual critique of such fundamentalism and arguing that, in an interesting corollary to Modi’s purported silence, it is Bhansali’s strategy of indirection – addressing contemporary events via a historical tale – that has paradoxically resulted in the film’s overwhelming success.